Studies on anaerobic fermentation of undiluted dairy cattle waste under mesophilic condition - SINGH, RAVI PRATAP (Indian Journal of Dairy Science, 2017)
AbstractThe higher dilution of substrate with water in the conventional anaerobic fermentation process demands for larger digester size and higher operating cost to handle a large volume of substrate water mix.Due to its lower water content the  digestate of dry / solid state anaerobic fermentation is much easier to handle than conventional process. Studies on anaerobic biodegradation of undiluted dairy cattle waste under dry / solid state fermentation (1:0 substrate-water ratio) and conventional (1:1 substrate-water ratio) were carried out at (35 ± 1ºC) to study biogas production, change in pH, total volatile solids removal efficiency (TVSRE) and biodegradation of substrates for eighty days so as to reach final yield. It was observed that specific biogas production under dry anaerobic condition was 0.84 1g-1 VS destroyed as compared to 0.79 1g-1 VS destroyed in conventional process. The pH of substrates under both the processes remained close to each other in the range of 6.3 to 7.4 however, the TVS removal efficiency was higher under conventional process. The total percent biodegradation of 36.76 and 47.49 % were observed under dry anaerobic and conventional process respectively. It can be estimated that3.6×1010 m3  of biogas could be generated from about 900 million tonnes of cattle dung annually in India.